2021
DOI: 10.1136/bmjopen-2021-050051
|View full text |Cite
|
Sign up to set email alerts
|

Association of the patterns of use of medications with mortality of COVID-19 infection: a hospital-based observational study

Abstract: ObjectivesSARS-CoV-2 enters cells using the ACE2 receptor. Medications that affect ACE2 expression or function such as angiotensin receptor blockers (ARBs) and ACE inhibitors (ACE-I) and metformin have the potential to counter the dysregulation of ACE2 by the virus and protect against viral injury. Here, we describe COVID-19 survival associated with ACE-I, ARB and metformin use.DesignThis is a hospital-based observational study of patients with COVID-19 infection using logistic regression with correction for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The main mechanism was suggested to be the blocking of the active role of angiotensin receptor-1 on SARS-CoV-2 entry into cells by soluble angiotensin-converting enzyme 2 [ 19 ]. Supporting the results, initiation or continuation of RAS blocker reduced the death risk, whereas discontinuation increased the risk [ 20 ]. A recent meta-analysis indicated no significant benefit or harm from RAS blocker use for either susceptibility, illness severity or mortality of COVID-19 infection [ 21 ].…”
mentioning
confidence: 59%
“…The main mechanism was suggested to be the blocking of the active role of angiotensin receptor-1 on SARS-CoV-2 entry into cells by soluble angiotensin-converting enzyme 2 [ 19 ]. Supporting the results, initiation or continuation of RAS blocker reduced the death risk, whereas discontinuation increased the risk [ 20 ]. A recent meta-analysis indicated no significant benefit or harm from RAS blocker use for either susceptibility, illness severity or mortality of COVID-19 infection [ 21 ].…”
mentioning
confidence: 59%
“…Wang et al 44 analyzed 39,829 T2D patients treated with metformin or another glucose lowering drug and verified that the prescription of metformin in primary care does not influence susceptibility to COVID-19, neither COVID-19 related mortality (HR 0.89; 95 % CI 0.74–1.07). On the analysis of 9532 United States (US) Veterans with COVID-19, Wallace et al 45 found a reduced risk of mortality with the maintenance of metformin during hospitalization (OR 0.35; 95 % CI 0.28–0.45) and with its initiation at admission (OR 0.19; 95 % CI 0.07–0.47) and an increased risk of mortality with its withdrawal (OR 1.54; 95 % CI 1.30–1.82). Orioli et al 46 analyzed diabetic patients with confirmed COVID-19 and compared survivors to non-survivors, and confirmed that the latter were less often treated with metformin ( p = 0.036).…”
Section: Resultsmentioning
confidence: 99%
“…The safety of continued ACEi and ARB medication in patients with COVID-19, where needed, is supported by recent randomized clinical trials. This study expands on these conclusions by suggesting that metformin, ACEi, and ARB therapy may be continued or started to improve COVID-19 survival [ 11 ].…”
Section: Reviewmentioning
confidence: 89%